A Serious Medical Case Confirming the Significance of Clinical Pharmacists’ Role Inside Community Pharmacists - Amer, Ahmed; Osman, Samir (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2025)
Diclofenac and ketorolac are prescribed as nonsteroidal anti-inflammatory drugs (NSAIDs) used to manage pain and inflammation. However, co-administration of them could lead to serious health problems. We seek to highlight the potential dangers of their concurrent use. We discuss the increased risk of severe gastrointestinal complications, including ulceration, bleeding, and perforation, associated with combining these medications. The case emphasizes the importance of clinician awareness of this drug interaction and advocates for safer prescribing practices. Also, we shed light on the significant role of clinical pharmacists in each community pharmacy, hospital, and medical centre. Keywords: Diclofenac, Ketorolac, Drug-Drug Interactions, Clinical pharmacist, Community Pharmacy